Efficacy of Aliskiren/Hydrochlorothiazide Combination for the Treatment of Hypertension: A Meta-Analytical Approach - Morgado, Manuel (2011)
Background: Single-pill combinations of aliskiren/hydrochlorothiazide have recently been approved by the European Medicines Agency for the treatment of hypertension. Objective: This study aimed to assess the antihypertensive efficacy of aliskiren/hydrochlorothiazide combination in reducing systolic and diastolic blood pressure in hypertensive patients. Methods: A search in International Pharmaceutical Abstracts, MEDLINE, The Cochrane Library and ISI Web of Knowledge was performed from 2000 to November 2009, to identify randomized, double-blind, clinical trials using aliskiren/hydrochlorothiazide for the treatment of hypertension. Studies were included if they evaluated the antihypertensive efficacy of aliskiren/hydrochlorothiazide in patients with mild or moderate essential hypertension and age 18 years. The meta-analytical approach calculated the weighted average reductions of systolic and diastolic blood pressure for each daily dosage combination. Results: We included 5 clinical trials testing several combinations of aliskiren/hydrochlorothiazide and containing data on 5448 patients. In all studies blood pressure was assessed at inclusion (baseline) and after 8 weeks of therapy. Blood pressure reductions and control rates were significantly (p < 0.05) higher with the aliskiren/hydrochlorothiazide combinations than with placebo and the same doses of aliskiren or hydrochlorothiazide alone. The weighted mean reductions (mm Hg) from baseline of systolic and diastolic blood pressure for each aliskiren/hydrochlorothiazide combination were: -15.8/- 10.3 (150/25 mg); -15.9/-11.8 (300/12.5 mg); -16.9/-11.6 (300/25 mg). Blood pressure control rates (%) for the above combinations were, at least, respectively: 43.8, 50.1 and 51.9. Conclusions: Aliskiren/hydrochlorothiazide provided clinically significant additional blood pressure reductions and improved blood pressure control rates over aliskiren or hydrochlorothiazide monotherapy.